Construction and demolition wastes and its management: a case study in Klang Valley, Malaysia - Eusuf, Muhammad Abu; Zainon, Nurulazwa; Abdullah @ Sudin, Handzalah; Ibrahim, Mansor; Islam, Rafikul (2010)
Many activities in construction and demolition projects are generally considered as complicated and unfriendly that may affect surrounding environment and public health. Construction, remodeling, repairing or demotion works of buildings and roads generate large amounts of hazardous and nonhazardous materials. This study highlights the major types of wastes and the specific causes of their generation. We also discuss the present ways of managing those materials. The paper concludes by providing recommendations on how to better manage the C&D wastes. As a case study, Klang valley in Malaysia has been considered. Major construction activities were taken place in Klang Valley and its surrounding areas include Federal Territory of Kuala Lumpur. In the present research project, a modest attempt has been made to highlight a number of issues in waste management, particularly C&D waste management in the Klang valley of Malaysia.